Annotations, Appendices, Adaptations: Recent Work on H. G. Wells's Scientific Romances. - Ruddick, Nicholas (Science Fiction Studies, 2005)
Reviews three books. "The War of the Worlds," by H. G. Wells, edited by Martin A. Danahay; "The Island of Dr. Moreau," by H. G. Wells; "H. G. Wells: Six Scientific Romances Adapted for Film," 2nd ed., by Thomas C. Renzi.